PEMANFAATAN INTERNET MARKETING DALAM PEMASARAN PRODUK UNGGULAN PERTANIAN PROVINSI GORONTALO The Use of Internet As Marketing Media of Agriculture Prominent of Gorontalo Province - Asriani Asriani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2011)
AbstractThe aim of the research is to analyze utilization of internet marketing in promoting the prominent agriculture products in order to increase investment in the Province of Gorontalo, and the shortcoming in utilizing internet marketing. The source informant of this research consisted of related officials in the Agriculture and Food Security Department and the Investment Board of the Province of Gorontalo, the website administrator and some agriculture businessman. The data collected through a deep interview, observation upon the website content and the Customer Relationship Management from the marketing communication view. The result shows that the internet marketing utilization by the Agriculture and Food Security Department of the Province of Gorontalo has not been fully utilized because the content that managed by the website administrator contains information that considered not important by the customer (visitor) so that the decision making process is difficult to take. However, by the interactive facility that is part of the CRM, this mater can be minimized by the administrator by creating two-way communication. Beside that, by managing a good relationship with the prospective investor as well as the existing investor that run their investment through CRM, this thing can contribute in increasing investment value in the Province of Gorontalo. From this research also found that the shortcoming in utilizing internet marketing is more to the short of the website administrator knowledge about the website content that considered valuable to the web user. The website administrator still not capable in understanding the need of the web user.